Tree-rings, historic documents, and interpreting past landuse and environments in the Upper Greybull River Watershed, northwestern, Wyoming - Reiser, Marcy L., author; Todd, Lawrence C., 1954-, advisor; LaBelle, Jason M., committee member; Coleman, Robert O., committee member; Sherman, Kathleen A., committee member (Colorado State University. Libraries, 2010)
Set in a high montane Engelmann spruce parkland in the central Absaroka Mountains of northwestern Wyoming, this thesis combines dendrochronology, archaeology, and data from historic documents to explore past human activity and climate in the Upper Greybull River Watershed. Based on early Euro-American accounts of the region, and its rugged remoteness, this harsh environment might seem an unlikely place for past human groups to survive and thrive. However, research conducted in the area since 2002, as part of the Greybull River Sustainable Landscape Ecology (GRSLE) project, reveals a dynamic environment rich with both prehistory and history and one that illuminates the past but just as quickly obscure and erase it. As a snapshot of ongoing research, this thesis presents tree-ring crossdating results for four historic cabins and associated structures collected prior to the Little Venus fire of 2006, including crossdates from a historic cabin that burned to the ground. Crossdating results are also presented for culturally modified trees in the area, including culturally peeled trees, and for a "ghost forest," which may represent the remnants of an ancient forest that succumbed to fire in the late-1400s to mid-1600s. Based on these crossdated samples, a preliminary standardized index of annual tree-ring growth, or master chronology, has been established which extends the tree-ring chronology back to 1260. This master chronology was then compared to historic documents from the region and accounts by early settlers of environmental conditions in the Upper Greybull River Watershed. This comparison has resulted in a more complex and nuanced understanding of past climate and human landuse, as well as highlighting stories about the past that only trees and historic accounts can tell. This thesis is part of an ongoing and urgent effort to collect, preserve and crossdate tree-ring samples from this fire-prone region. Like much of the West, forests in this area have been devastated by a recent bark beetle epidemic, posing a significant threat to cultural resources, especially those made of wood.